Feasible earnings momentum in the U.S. stock market: An investor's perspective - Christopher Krauss; Daniel Beerstecher; Tom Krüger (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Wirtschaftspolitik und Quantitative Wirtschaftsforschung (IWQW), 2015)
This paper examines earnings momentum strategies in the U.S. stock universe from an investor's perspective. Specifically, we use the software Stock Investor Pro from the American Association of Individual Investors (AAII) to obtain the composition of the U.S. stock universe from 2005-2015 on a weekly basis. Raw data is validated via Thomson Reuters Datastream. Next, we implement long-only and long-short earnings momentum strategies based on earnings estimates revisions. Furthermore, we develop a novel price-earnings momentum strategy by intertwining earnings momentum with a 52 week high strategy. Our findings re-confirm the high returns of the classical earnings momentum strategy with equal-weighted raw returns of 23.6 percent p.a. for the monthly long-only strategy. Most importantly, we find large parts of these raw returns to be robust to a wide spectrum of systematic sources of risk and feasible in light of market frictions, such as trading costs, liquidity constraints and microstructure effects. The enhanced price-earnings momentum strategy invests in earnings momentum stocks with below-median distance to their 52 week high. This simple alteration leads to an improvement of annualized raw returns to 31.0 percent, equally robust to systematic sources of risk and market frictions. We conclude that earnings momentum strategies are feasible and continue to pose a serious challenge to the semi-strong form of market efficiency.
Keywords: 330; earnings momentum; price momentum; market efficiency; return predictability